Autoantibodies to killer cell immunoglobulin‐like receptor 3DL1 in patients with systemic lupus erythematosus. (14th December 2018) - Doi, A.; Kano, S.; Asano, M.; Takahashi, Y.; Mimori, T.; Mimori, A.; Kaneko, H.
Summary: A genetic variant of the killer immunoglobulin‐like receptor 3DL1 ( KIR3DL1 ) has been found in patients with systemic lupus erythematosus (SLE). Herein, we investigated the presence of autoantibodies to KIR3DL1 in a cohort of patients with SLE. We tested sera from 28 patients with SLE, 11 patients with rheumatoid arthritis (RA) and 17 healthy control subjects for anti‐KIR3DL1 activity by an enzyme‐linked immunosorbent assay (ELISA) using recombinant KIR3DL1‐enhanced green fluorescent protein (EGFP) and EGFP proteins. Anti‐KIR3DL1 antibodies were detected in 22 (79%) of the 28 patients with SLE, whereas they were present in only three (27%) of the 11 patients with RA examined. Notably, 10 (91%) of the 11 samples from patients with SLE prior to therapy had anti‐KIR3DL1 antibodies. None of the samples from healthy donors were positive for the antibodies. Here, we report the presence of anti‐KIR3DL1 antibodies in the sera of patients with SLE for the first time. Anti‐KIR3DL1 autoantibodies may be involved in the pathogenesis of autoimmune diseases. Abstract : Autoantibodies to KIR3DL1 are present in the sera of patients with SLE, which could be a applied as a novel diagnostic marker of SLE.